'Temporarily' Abroad: Partisan Organisation and Mobilisation outside Australia. Issue 4 (28th July 2020) - Gauja, Anika
Abstract: This article explores the relationship between partisan organisation outside a country of origin and the voting rights and migration patterns of its citizens. Using Australian political parties operating overseas as case studies, it examines the extent to which the electoral context of expatriate voting influences why and how parties establish organisational structures abroad. Electoral law in Australia allows citizens to vote while living overseas only for a limited period—as long as they intend to return to Australia within six years. Because of this relatively limited opportunity, we might expect party organisations abroad to exist primarily to mobilise support at election times in areas where there are high concentrations of Australian expatriate voters, rather than create lasting communities of partisan supporters. The article finds, in line with this expectation, that 'parties abroad' are relatively modest, geographically rooted in cities with large expatriate populations and facilitated by online and social media technologies.